2008
DOI: 10.1523/jneurosci.4651-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Signaling Controls Intracortical Migration and Final Distribution of GABAergic Interneurons

Abstract: Functioning of the cerebral cortex requires the coordinated assembly of circuits involving glutamatergic projection neurons and GABAergic interneurons. Although much is known about the migration of interneurons from the subpallium to the cortex, our understanding of the mechanisms controlling their precise integration within the cortex is still limited. Here, we have investigated in detail the behavior of GABAergic interneurons as they first enter the developing cortex by using time-lapse videomicroscopy, slic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
274
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(293 citation statements)
references
References 50 publications
(62 reference statements)
18
274
0
1
Order By: Relevance
“…Chemokine signalling through CXCL12/CXCR4 is a common mechanism controlling the migration of several cell types along the body axis, such as hematopoietic progenitor cells 40 , vascular endothelial cells 41 , melanocytes 42 and tumour cells 43,44 . In addition to the present results, it has been reported that in the CNS, in addition to CR cells, the migration of cerebellar granule precursors 34 , cortical interneurons 23 , microglia 45 , neural precursor cells 46 , and certain brain tumour cells 33 is also dependent on CXCL12/CXCR4…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Chemokine signalling through CXCL12/CXCR4 is a common mechanism controlling the migration of several cell types along the body axis, such as hematopoietic progenitor cells 40 , vascular endothelial cells 41 , melanocytes 42 and tumour cells 43,44 . In addition to the present results, it has been reported that in the CNS, in addition to CR cells, the migration of cerebellar granule precursors 34 , cortical interneurons 23 , microglia 45 , neural precursor cells 46 , and certain brain tumour cells 33 is also dependent on CXCL12/CXCR4…”
Section: Discussionsupporting
confidence: 84%
“…The interactions between both nectins control radial migration by acting in concert with Reelin and Cdh2 to promote interactions between migrating neurons and CR cells 21 . The activity of CXCL12 and its receptors has been found to play a role in controlling the migration of other cortical neurons (for example, GABAergic interneurons) that are also influenced by the action of Semaphorins and their receptors 22,23 . Semaphorins and their receptors, Plexins and Neuropilins, have emerged as important cellular cues regulating key developmental processes, as neuronal migration and axonal guidance 24 .…”
mentioning
confidence: 99%
“…Specifically, disrupted CXCL12/CXCR4 signaling results in premature migration of GABAergic interneurons into the cortical plate and, consequently, aberrant laminar and regional positioning of cortical interneurons (19,20). Furthermore, GABAergic interneurons migrating through the marginal zone, including calbindin ϩ interneurons, exhibit slow multidirectional movement, a local positioning phase, before descent and integration into the cortical plate (21,22 integrin-mediated cell migration through the cortical marginal zone may lead to temporal and spatial alterations in the local positioning phase of interneurons and subsequent deficits in the integration of interneurons within the cortical plate.…”
Section: Altered Migration and Positioning Of Interneurons In The Absmentioning
confidence: 99%
“…We now report in the LgDel mouse-in which recent studies (18)(19)(20) suggest that cortical circuit assembly and function is compromised-a mechanistic relationship between diminished 22q11.2 dosage and a key molecular pathway that regulates interneuron migration during cortical development. LgDel interneuron phenotypes reflect interneuron-specific disruption of cytokine receptor Cxcr4, which has been shown to influence placement, migratory trajectory, and motility of these cells during cortical development (21)(22)(23)(24)(25). Thus, we define a relationship between 22q11.2DS, a compelling example of a copy number variant (CNV) syndrome thought to cause cortical circuit disorders, and Cxcr4-mediated signaling, an established mechanism that ensures normal cortical interneuron development.…”
mentioning
confidence: 99%